DOI: 10.30707/etd2014.paulson.d
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Cooperating Teachers Concerning the Student Teaching Field Experience

Abstract: This study explored the views of cooperating teachers on (a) their work with student teachers and university supervisors, and (b) ways to improve the student teaching process. In a mixed-methods sequential explanatory study, 153 cooperating teachers answered closed-and open-ended questions using an electronic survey; then a subset of 12 participated in follow-up interviews. All participants taught at rural or semi-rural middle schools and high schools in Central Illinois; all had experience with student teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 57 publications
(105 reference statements)
0
8
0
Order By: Relevance
“…Phase I provided several challenges that cooperating teachers identified themselves encountering. Some were similar but did not fully match up to those found by Paulson (2014) when conducting a study on the challenges that cooperating teacher face.…”
Section: Challenges Cooperating Teachers Faced Supervising a Student mentioning
confidence: 74%
See 2 more Smart Citations
“…Phase I provided several challenges that cooperating teachers identified themselves encountering. Some were similar but did not fully match up to those found by Paulson (2014) when conducting a study on the challenges that cooperating teacher face.…”
Section: Challenges Cooperating Teachers Faced Supervising a Student mentioning
confidence: 74%
“…Literature discovered during this study provided other studies related to the effects the student teaching experience had on the cooperating teacher. Paulson (2014) investigated the effects the student teaching experience had on cooperating teachers and examined the relationship between the cooperating teacher and the student teacher.…”
Section: Cooperative Teachermentioning
confidence: 99%
See 1 more Smart Citation
“…Paulson (Paulson & Latham, 2015) to examine the views of cooperating teachers in relation to their work with student teachers and university supervisors and from a 2016 a pilot study (Bruemmer, 2016) investigating similar concepts. The pilot study indicated that cooperating teachers were interested in helping to support the next generation of teachers, and many of them have invested in the education field through earning higher degrees, participating multiple times as a cooperating teacher, and teaching for multiple years.…”
Section: Instrumentationmentioning
confidence: 99%
“…Dawn Paulson (Paulson & Latham, 2015). To support the validity and reliability of the survey, a pilot study was conducted that examined whether the survey items indeed measured the phenomenon under study.…”
Section: Instrumentationmentioning
confidence: 99%